INVESTIGATING THE ROOT CAUSES OF THE RISING MENTAL HEALTH ISSUES AMONG GENERATION Z - Daffa Hegian Abiy Ahmed; Tias Sekar Sari; Rizqina Ritnaning Febriyanti; Najwa Aulia Zahra (Education Studies and Teaching Journal (EDUTECH), 2025)
This study aims to examine the root causes of the increase in cases of mental disorders in Generation Z, a demographic group born between 1997 and 2012, and known to be very familiar with the digital world. Mental disorders are defined as health conditions that affect a person's thoughts, feelings, or responses, including anxiety, depression, and stress that can cause physical symptoms. Determinants of mental health include socioeconomic, biological, and environmental aspects. Compared to previous generations, Gen Z shows higher levels of stress, anxiety, and depression. This study uses a literature review method, analyzing and summarizing previous studies from trusted academic databases such as Google Scholar, Sinta, and Garuda with keywords such as "causes of mental disorders", "mental disorders of Gen Z", and "generation Z". The results of the analysis indicate that the increase in mental disorders in Gen Z is caused by several main factors, namely intensive digital media use and internet addiction, family environment and parenting styles, unhealthy living environments, and negative peer influence. In addition, socioeconomic status also contributes to mental vulnerability. Gen Z's increased awareness and openness in discussing mental health issues has also made these cases more visible and documented. The 2018 RISKESDAS data shows that the prevalence of mental health disorders in adolescents aged 15 and above reached 6.1%, equivalent to 11 million people in Indonesia. Globally, one in seven children aged 10 to 19 experiences a mental disorder, yet most do not receive adequate treatment. Therefore, a thorough understanding of these factors is crucial for developing effective prevention and treatment strategies.